Understanding the influence of increasing forest biomass on inter-annual evapotranspiration regime using the Budyko framework at forest-dominated landscape - Wonjin Kim; Soyoung Woo; Seongjoon Kim (Ecological Indicators)
This study investigated the influence of increasing forest biomass on the evapotranspiration regime using the Budyko framework across annual and inter-annual scales. In the forest-dominated watershed, Yongdam Dam Basin, the Budyko curves were derived for past and present forest biomass conditions revealed significant shifts, characterized by increasing shape factors indicating a transition toward an energy-limit state. The seasonal analysis showed that spring and autumn had higher sensitivity, as these seasons play a key role in balancing water and energy due to their transitional nature. Summer and winter exhibited relatively low sensitivity, with summer stabilized by concentrated rainfall and forest buffering effects, while winter’s minimal hydrological activity resulted in reduced responsiveness. Sensitivity analyses across aridity and moisture conditions underscored the consistent amplification of ET sensitivity with increasing forest biomass, particularly within a certain range of aridity conditions. These findings provide critical insights into the interaction between vegetation and hydrological processes, emphasizing the importance of season-specific management strategies to optimize water resource allocation and mitigate the impacts of climate variability.